2021
DOI: 10.1080/16066359.2021.1876847
|View full text |Cite
|
Sign up to set email alerts
|

May I have your attention, please? Methodological and analytical flexibility in the addiction stroop

Abstract: Background: Theoretical models of addiction predict that an attentional bias toward substance-related cues plays a role in development and maintenance of addictive behaviors, although empirical data testing these predictions are somewhat equivocal. This may in part be a consequence of substantial variability in methods used to operationalize attentional bias. Our aim was to examine the variability in key design and analysis decisions of the addiction Stroop. Method: Using a pre-registered design, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…functional magnetic resonance imaging [63]), such flexibility is associated with increased false-positive findings, particularly when paired with selective reporting and publication bias [64,65]. Indeed, Jones et al [62] found that key aspects of design and analysis decisions were not disclosed when employing the addiction Stroop task, and our review of the alcohol-attentional bias literature indicates that only one study (1.56%) reported design and analysis decisions a priori through study preregistration.…”
Section: Variability In Experimental Design and Analysis Decisionsmentioning
confidence: 80%
See 3 more Smart Citations
“…functional magnetic resonance imaging [63]), such flexibility is associated with increased false-positive findings, particularly when paired with selective reporting and publication bias [64,65]. Indeed, Jones et al [62] found that key aspects of design and analysis decisions were not disclosed when employing the addiction Stroop task, and our review of the alcohol-attentional bias literature indicates that only one study (1.56%) reported design and analysis decisions a priori through study preregistration.…”
Section: Variability In Experimental Design and Analysis Decisionsmentioning
confidence: 80%
“…Indeed, Jones et al . [62] found that key aspects of design and analysis decisions were not disclosed when employing the addiction Stroop task, and our review of the alcohol‐attentional bias literature indicates that only one study (1.56%) reported design and analysis decisions a priori through study preregistration.…”
Section: Methodological Issuesmentioning
confidence: 85%
See 2 more Smart Citations
“…Some discrepancies in reliability scores may also be accounted for by variation in the exact parameters selected for the tasks; the exact specifications of a given task may vary wildly (e.g. Jones, Worrall, Rudin, Duckworth, & Christiansen, 2021 ; Parsons, Kruijt, & Fox, 2019 ). There are also often numerous measures within a task and/or different indices that may be used for performance assessment.…”
Section: Discussionmentioning
confidence: 99%